2008
DOI: 10.3748/wjg.14.2142
|View full text |Cite
|
Sign up to set email alerts
|

Necrotizing enterocolitis: A multifactorial disease with no cure

Abstract: INTRODUCTIONNecrotizing enterocolitis (NEC) is an inflammatory bowel disease of neonates and remains one of the most common gastrointestinal emergencies in newborn infants [1] . Onset of NEC is often within the first three months of life and neonates who are of extremely low birth weight (< 1000 g) and under 28 wk gestation are the most susceptible [2] . Full term neonates account for 10% of all NEC cases while premature infants account for 90% [3] . With an incidence rate of 1%-5% for all newborns admitted to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
120
1
38

Year Published

2009
2009
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 163 publications
(169 citation statements)
references
References 201 publications
(405 reference statements)
2
120
1
38
Order By: Relevance
“…It is known that any abnormality in the ecosystem of the gastrointestinal tract may result in a pathological process potentially leading to NEC (3). It is suspected that abnormal colonization of the gastrointestinal tract or an unfavorable balance between commensal and pathogenic bacteria is part of the pathogenesis of NEC (4)(5)(6). It has been suggested that the ability of microflora to invade the epithelium and ferment unabsorbed nutrients (7), and the colonization by various bacterial pathogens in a sufficiently vulnerable host (8) could promote the development of NEC.…”
mentioning
confidence: 99%
“…It is known that any abnormality in the ecosystem of the gastrointestinal tract may result in a pathological process potentially leading to NEC (3). It is suspected that abnormal colonization of the gastrointestinal tract or an unfavorable balance between commensal and pathogenic bacteria is part of the pathogenesis of NEC (4)(5)(6). It has been suggested that the ability of microflora to invade the epithelium and ferment unabsorbed nutrients (7), and the colonization by various bacterial pathogens in a sufficiently vulnerable host (8) could promote the development of NEC.…”
mentioning
confidence: 99%
“…Necrotizing enterocolitis (NEC) is the main cause of morbidity and mortality in very low birth weight neonates 1,2 . Due to an unsatisfactory response to treatment and lack of effective prevention, it is estimated that 20% to 40% of newborns with NEC require surgical treatment 2 .…”
Section: ■ Introductionmentioning
confidence: 99%
“…Ninety percent of cases occur in preterm infants, with the greatest risk in the smaller, more premature infants (Lin et al 2008;Thompson and Bizzarro 2008;Schnabl et al 2008). Compared with an overall incidence rate of 1% to 7.7%, up to 7% to 14% of very-low-birth-weight infants (< 1,500 g) are diagnosed with NEC (Kosloske 1994;Neu 2005).…”
mentioning
confidence: 99%